The Analysis of Teacher Politeness during Learning Process in Bilingual Community School - Kadek Katarina Dewi Kurniawati; I Wayan Pastika; Anak Agung Putu Putra (Riviera Publishing, 2025)
This study aims to analyze the politeness strategies employed by teachers during the learning process at the Bilingual Community School. Teacher communication in the classroom is significantly influenced by the use of polite utterances, especially in a bilingual setting where both linguistic and cultural differences shape the dynamics of interaction. This research uses a qualitative method, with data collected through direct observation and audio recordings of teacher utterances during classroom activities. The subjects of the study were reception class teachers actively engaged in bilingual instruction. The findings identified 12 teacher utterances applying various politeness strategies, such as positive politeness, negative politeness, bald on-record, and off-record strategies. These strategies were not used arbitrarily but were adapted to align with learning objectives, classroom management goals, and situational context. The study highlights how politeness strategies enhance teacher-student rapport, classroom engagement, and the overall effectiveness of communication in a multilingual educational environment, providing insight for educators in similar contexts.